Peramalan Pembiayaan Modal Kerja pada Bank Syariah di Indonesia: Aplikasi Model ARIMA - Firman, Asmen Junaidi; Binangkit, Intan Diane (SUSTAINABLE, 2025)
This study aims to forecast working capital financing for Islamic Commercial Banks (BUS) and Sharia Business Units (UUS) in Indonesia using the ARIMA model as a basis for strategic decision-making. The research object is the total working capital financing of BUS and UUS based on monthly data from January 2017 to March 2025. The research stages include descriptive statistical analysis, stationarity testing with Augmented Dickey-Fuller, identification of ACF/PACF patterns, parameter estimation and significance testing, residual validation, and selection of the best model based on AIC, SBC, and MSE criteria. The analysis results show the ARIMA(8,1,7) model as optimal with AIC 18.6304 and MSE 6,792,148, while residuals meet white noise and normality assumptions. The 12-month forecast (April 2025–March 2026) indicates an increasing financing trend from Rp130.3 trillion to Rp148.98 trillion, despite moderate fluctuations in some months. The discussion confirms that ARIMA captures historical dynamics and external volatility, enabling forecast integration into decision systems for fund allocation optimization and liquidity risk mitigation. In conclusion, ARIMA(8,1,7) proves accurate for predicting BUS-UUS working capital financing and supports Islamic banking management strategies in Indonesia.